Using niche modelling and human influence index to indicate conservation priorities for Atlantic forest deer species - Oliveira, Márcio Leite de [UNESP]; Peres, Pedro Henrique de Faria [UNESP]; Grotta-Neto, Francisco [UNESP]; Vogliotti, Alexandre; Passos, Fernando de Camargo; Duarte, José Maurício Barbanti [UNESP] (Elsevier, 2022)
To prioritise conservation actions and management strategies for threatened forest deer species at the Atlantic forest, we aimed to identify and describe the most suitable habitat areas for forest deer species and to indicate conservation measures for state agents and local communities. We adopt an approach based on ecological niche modelling, key variable thresholds and spatial analyses. In addition, we associated our approach with a human influence index, an invasive species dataset of occurrences, protected area cover and IUCN category. We indicate 2 % (484 km2) of the Atlantic forest cover as conservation priority areas (CPAs). Of these, 56.8 % are outside protected areas, 20.7 % are inside IUCN categories i, ii and iii protected areas, 19.9 % are inside IUCN categories iv, v, and vi protected areas, and 2.6 % are inside indigenous areas. Also, we indicate the most relevant protected areas for deer conservation in the Atlantic forest. The CPAs were classified into more human-influenced areas (MHIA) and less human-influenced areas (LHIA), and we identified 21 significant (greater than120 km2) continuous CPAs outside protected areas. We highlight actions in several perspectives of human influence, governance levels and law protection that would rationalise the use of funds and human resources.
Keywords: Global human influence index; Maxent; Mazama; Protected areas; Spatial analysis; Wildlife management